Equality rights as legal and factual optimization requirements: problems of knowledge and accumulation due to formal principles - Feng, Wei (2025)
The theoretical-structural question of constitutional dogma refers to the relationship between equality rights and subjective rights, both in terms of constitutional provisions on equality rights and the dimension of equality of other rights. There is a parallel between equality in relation to acts (as prima facie abstract and negative equality rights) and negative legal freedoms, while “factual” equality in relation to consequences (prima facie abstract and positive equality rights) reflects the dimension of equality of rights of provision. There are three possible models for examination: the prohibition of arbitrariness (as a model of rules), the proportionality test with or without the scope of protection-intervention-restriction scheme (both as models of principles). A formula for the concrete weighting of equality rights must be observed in the balancing of the accumulation of legal and “factual” equality with other fundamental rights.